Of Cockroaches and Symbionts: Recent Advances in the Characterization of the Relationship between Blattella germanica and Its Dual Symbiotic System - Latorre, Amparo; Domínguez-Santos, Rebeca; García-Ferris, Carlos; Gil, Rosario (Life (Basel, Switzerland), 2022)
Mutualistic stable symbioses are widespread in all groups of eukaryotes, especially in insects, where symbionts have played an essential role in their evolution. Many insects live in obligate relationship with different ecto- and endosymbiotic bacteria, which are needed to maintain their hosts’ fitness in their natural environment, to the point of even relying on them for survival. The case of cockroaches (Blattodea) is paradigmatic, as both symbiotic systems coexist in the same organism in two separated compartments: an intracellular endosymbiont (Blattabacterium) inside bacteriocytes located in the fat body, and a rich and complex microbiota in the hindgut. The German cockroach Blattella germanica is a good model for the study of symbiotic interactions, as it can be maintained in the laboratory in controlled populations, allowing the perturbations of the two symbiotic systems in order to study the communication and integration of the tripartite organization of the host–endosymbiont–microbiota, and to evaluate the role of symbiotic antimicrobial peptides (AMPs) in host control over their symbionts. The importance of cockroaches as reservoirs and transmission vectors of antibiotic resistance sequences, and their putative interest to search for AMPs to deal with the problem, is also discussed.